The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.19030/jabr.v31i3.9228
|View full text |Cite
|
Sign up to set email alerts
|

Implement Fama And French And Capital Asset Pricing Models In Saudi Arabia Stock Market

Abstract: This paper applies two of the famous asset pricing models in finance (Capital Assent Pricing model and Fama and French 1993 three factor model) in an emerging market with an Islamic Culture: Saudi Arabia Market (Tadwal), Generalized Methods of Moments and t Test statistical techniques were used to find the coefficients and to compare between real and expected returns.The results show that Fama and French 1993 model has more explanatory power and do a better job in explaining the changes in stock returns than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(5 reference statements)
2
2
0
Order By: Relevance
“…In addition this is because SMB and HML in the company are considered to have a very important role for the sustainability of the company, so that the SMB and HML variables can explain the ability to generate returns for investors. The results of other studies supporting this study were carried out by Aldaarmi, et al (2015) whose results show that the Fama and French 1993 model has more clear power and power in explaining changes in stock returns.…”
Section: The Effect Of Three Factors Pricing Model On Excess Stock Resupporting
confidence: 82%
“…In addition this is because SMB and HML in the company are considered to have a very important role for the sustainability of the company, so that the SMB and HML variables can explain the ability to generate returns for investors. The results of other studies supporting this study were carried out by Aldaarmi, et al (2015) whose results show that the Fama and French 1993 model has more clear power and power in explaining changes in stock returns.…”
Section: The Effect Of Three Factors Pricing Model On Excess Stock Resupporting
confidence: 82%
“…The outperformance of the three-factor model over the traditional CAPM has also been found in the Indian stock market by Bartholdy and Peare (2005). Similar evidences were being reported by Taneja (2010) and Aldaarmi et al (2015) in the Indian and Saudi Arabian stock markets, respectively. Walid (2009) in his paper provided stronger support for the characteristic model rather than Fama-French three-factor model in explaining return dynamics of the Japanese stock market.…”
Section: Literature Reviewsupporting
confidence: 77%
“…They also found that the size and value factors (SMB & HML) are not sufficient to explain the cross-section variance of expected returns either individually or jointly with each other, but when the market factor (R M -R F ) is combined with the size and value factors (SMB & HML), this would increase the explanatory power of the model, where the results showed that the explanatory power of the (R M -R F ) individually was greater than the explanatory power of the total size and value. Aldaarmi et al (2015) examined the ability of the Capital Assets Pricing Model (CAPM) and Fama and French (1993) In this study we used monthly data for a sample of firms listed on the Egyptian Stock Exchange from January 2014 to December 2018 to examine the performance of the Fama-French three-factor model (1993) before and after adding the financial leverage factor as a risk factor, where we will try to identify the impact of financial leverage on the risk pricing in the Egyptian Stock Exchange by adding an additional risk factor reflecting Financial leverage to the Fama and French (1993) model, where the Fama and French (1993) model will be tested in its original form and re-tested after adding the additional risk factor. These data included:  Monthly stock returns.…”
Section: Jfsmentioning
confidence: 99%